THE EFFECTIVENESS OF VOCABULARY-BASED-INTEGRATED ACTIVITIES IN IMPROVING THE STUDENTSâ VOCABULARY COMMAND - Alimuddin, Andi Haeriati (Program Pascasarjana Universitas Negeri Makassar, 2015)
Andi Haeriati Alimuddin State University of Makassar Abstract Finding a method to be used in vocabulary teaching and learning to different learning style students is a big challenge for English teachers at SMA Negeri 1 Soppeng Riaja as the result of preliminary study found that the studentsâ vocabulary command is still low and the teacher promoted less awareness of the different studentsâ learning style in vocabulary learning. An explanatory research was conducted to investigate the effectiveness of Vocabulary-based Integrated Activities in improving the studentsâ vocabulary command by involving the second year students of natural science class of SMA Negeri 1 Soppeng Riaja in academic year 2012/2013. It is concluded from quantitative and qualitative findings that the Vocabulary-based Integrated Activities are: (1) most effective to improve the studentsâ vocabulary command in terms of knowing, understanding the words and how they are said and written; (2) most effective to improve the studentsâ vocabulary command in terms of using the words in written form; (3) effective to improve the studentsâ ability the studentsâ vocabulary command in terms of using the words in oral form; (4) able to cover all students with different learning style, because there is no significant difference of vocabulary command among visual, auditory, and haptic students after they were taught by the method. In addition, students have good perception of the Vocabulary-based Integrated Activities. Key words: Vocabulary-based Integrated Activities, Vocabulary Command Learning Style